Career Concerns As Public Good: The Role of Signaling for Open Source Software Development - Lena Abou El-Komboz; Moritz Goldbeck (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Much of today's software relies on programming code shared openly online. Yet, it is unclear why volunteer developers contribute to open-source software (OSS), a public good. We study OSS contributions of some 22,900 developers worldwide on the largest online code repository platform, GitHub, and find evidence in favor of career concerns as a motivating factor to contribute. Our difference-in-differences model leverages time differences in incentives for labor market signaling across users to causally identify OSS activity driven by career concerns. We observe OSS activity of users who move for a job to be elevated by about 16% in the job search period compared to users who relocate for other reasons. This increase is mainly driven by contributions to projects that increase external visibility of existing works, are written in programming languages that are highly valued in the labor market, but have a lower direct use-value for the community. A sizable extensive margin shows signaling incentives motivate first-time OSS contributions. Our findings suggest that signaling incentives on private labor markets have sizable positive externalities through public good creation in open-source communities, but these contributions are targeted less to community needs and more to their signal value.
Keywords: L17; L86; H40; J24; J30; 330; software; knowledge work; digital platforms; signaling; open source; job search